The influence of procedural, distributive and interactional justice on job satisfaction among members of the South African Police Academy: Thabong. - Gounden, Manisagaree (My University, 2018)
The purpose of this study was to examine the influence of procedural, distributive and interactional justice on job satisfaction among members of the South African Police Academy, Thabong. A critical function of the South African Police Service (SAPS) is to ensure that the inhabitants of South Africa are safe. Members of the SAPS need to be committed and have a high morale to ensure that the vision of the SAPS is fulfilled. This study advocates the application of the equity theory. People prefer to work in an environment that is perceived as just. Employees will experience satisfaction with their job in terms of equity when the equity theory is applied. However, inequity will lead to tension at the workplace. In order for the officers as employees of the SAPS to function effectively, it is essential for the SAPS to ensure that their employees are satisfied. In this study, a quantitative approach was applied to gain an understanding of the influence of organisational justice (OJ) dimensions (PJ, DJ, IJ) on job satisfaction (JS). This involved administering questionnaires to 234 employees who were attending management courses at the SAPS Academy, Thabong in the northern Free State province of South Africa. Two primary tests were used to assess the suitability of the data for factor analysis. These tests are the Kaiser-Meyer Olkin (KMO) measure of sampling adequacy and Bartlett’s test of sphericity. The Pearson correlation coefficient was used to examine the correlations among the constructs. A means analysis was conducted to assess the perceptions of the employees in respect of PJ, DJ, IJ and JS. Multiple regression analysis was executed to examine whether the independent variables of PJ, DJ and IJ predict the dependent variable JS. The Cronbach alpha coefficient test provided an adequate indication of reliability of the instrument. Face/ content, construct and convergent validity methods were applied to establish validity of the study. A positive relationship between the OJ and JS was found in this study. The SAPS will be able to improve the JS levels of SAPS officers by making positive improvements when applying OJ to influence the various elements of JS identified in this study. This will effectively enable SAPS officers to meet the challenge of providing improved service. The proper implementation of OJ will ultimately lead to the organisations success as well as the progression of its employees. Since the SAPS depends on human resources, the organisation is required to assess the current OJ practices and create a working environment that stimulates and motivates employees so that their JS levels increase. The recommendations proposed for this study offer vital information on OJ practices that could assist the SAPS to improve the perceptions of employees. Accordingly, the application can improve employees’ low morale resulting from unfairness and injustice, thereby increasing the JS levels amongst employees. The findings of the research may generate guidelines for OJ practices. Recommendations include a systematic and transparent reward system that recognises employees’ excellent performance and rewards them accordingly. Another recommendation is the creation of a well-structured consultative forum to grant employees an opportunity to provide management with their perceptions of unfair practices. Future research should extend to other sectors within the public sector environment, as well as expanding the research to include several other JS elements.
M.Tech (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: organisational justice, procedural justice, distributive justice, interactional justice, job satisfaction; South African Police Service.; Job satisfaction -- South Africa.; Justice -- South Africa.